Uji Penerimaan Konsumen terhadap Mutu Organoleptik Petis Ikan Situbondo dengan Metode Uji Kesukaan - Dewi Sarastani; Ima Kusumanti; Cecilia Eny Indriastuti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Fish paste is a local product which is a source of income for coastal communities in Situbondo Regency. Production of fish paste is still dominated by household business scale. In addition to paying attention to chemical and microbiological quality, it is necessary to pay attention to sensory quality to meet the quality and food safety requirementsof the paste. Even, organoleptic quality greatly determines consumer acceptance to buy products. This study aims to determine consumer acceptance of the organoleptic quality of four types of fish paste products produced by producers A, B, C, and D in Situbondo Regency. Testing on consumer acceptance is carried out by sensory testing using the hedonic test method. The sensory parameters tested included: color, aroma, taste, aftertaste, and overall acceptance of the paste. There are 9 hedonic scales used in this test, namely very dislike (1), really dislike (2), dislike (3), rather dislike (4), neutral (5), rather like (6), likes (7), likes very much (8), and likes very extremely (9). The numerical scale (1-9) is processed using ANOVA and Duncan's test. The results showed that the organoleptic quality of the four types of fish paste was rated somewhat neutral (5) to rather like (6). Among the four products, the fish paste D (5.84) and B (5.75) that are most accepted by consumers with characteristics: dark brown paste, the aroma of spices and fish are smelt, the savory taste is felt, the fishy aftertaste doesn't linger in the mouth, and the texture is homogeneous-elastic-soft. While the petis made by producer A got a preference value of 4.92 (ordinary) and the petis made by producer B with a preference value of 5.17 (ordinary).